The Camel Club - Baldacci, David (New York : Warner Books, 2005)
The Camel Club is a four-man group of Washington, D.C. misfits, that meet weekly to discuss political conspiracies they believe exist and what actions they might take. One night club members witness the murder of Secret Service employee Patrick Johnson, thus thrusting the wacky crew into the middle of a bigger conspiracy than they could ever have imagined.
Accelerated Reader AR
Keywords: Secret societies -- Fiction; Nuclear warfare -- Fiction; Conspiracies -- Fiction; Political fiction; Suspense fiction